A comparison between drug experimenters and non-experimenters regarding their participation to the social activities: İstanbul sample - Ögel, Kültegin; Ermağan, Eda; Eke, Ceyda Y.; Taner, Sevil (Journal of Dependence, 2007)
Objective: The goal of this study was to compare drug experimenters and non-experimenters regarding their participation to the social activities among 10th grade students in Istanbul. Method: Tenth grade students in age range of 15-17 of Istanbul were recruited for the study. The study has been done in 13 vocational, 24 public and 6 private schools that have been selected from different socioeconomic levels and regions of Istanbul. Results: The most frequent social activities that 10th grade students engage in have been found to be reading newspapers (%94,2), meeting with friends (%92,8) and doing sports (%83,6) whereas pop music was the most preferred type of music. Noticably, substance-nonexperimenters were more likely to read newspapers of 1.8 times, participate in a course of 1,48 times and read extracurricular books of 1,53 times than substance-experimenters. Riding car for recreation, going out for clubs/pubs, cafes and internet-surfing, going to internet cafes, going to Taksim and music concerts, soccer games were found to be higher for substance-experimenters, compared to substance-nonexperimenters. Conclusion: Our study revealed that substance-nonex-perimenters prefer goal-oriented, structured and individualistic social activities. Positive correlation was found between substance use and engagement in social activities that are out of monitoring and control, unstructured and have aim of being in crowded contexts just for spending leisure time.